REALISASI NILAI-NILAI AKHLAK PADA KITAB AKHLAK LIL BANIN DAN PENERAPANNYA PADA SISWA KELAS VB MI HIDAYATUL MUTA’ALIMIN TUBAN - Anisah, Zulfatun; Ainur Rhofiqoh, Siti; Fitriatul Ulya, Vita (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research aims to find out the extent of the moral values contained in the lil banin moral book and the obstacles in realizing these moral values in the daily lives of VB class students at MI Hidayatul Muta'alimin Medalem Senori Tuban. This research uses qualitative research using triangulation techniques. The research data sources were the class V homeroom teacher, ustad/ustadzah kitab akhlak lil banin and VB MI class student Hidayatul Muta'alimin. The results of this research show that the process of learning Lil Banin's book of morals uses several methods, namely: sorogan method, lecture method, memorization method, and exemplary method. From the research results, it turns out that many of the values in Lil Banin's book of morals have been implemented by students, such as shaking hands with parents, cleaning the room before studying. Always respect teachers by differentiating how to speak between teachers and friends. And students can respect older people and love younger ones. The obstacles experienced are students' varying morals, difficulty controlling students who like to sleep and many students who are indifferent to their fellow students so that there are students who feel isolated